Peran Regulasi Dalam Pengungkapan Informasi Keuangan Untuk Perlindungan Investor - Nur Fitriana; Naina Azzahra Herman; Nola Rahma Diny; Ria Crisna Sianturi (Jurnal Ekonomi dan Bisnis Digital, 2025)
A healthy and efficient capital market requires transparent and accountable financial information disclosure. This study examines the role of regulations in ensuring financial information disclosure that protects investors' interests. Effective regulations establish minimum standards for companies to provide relevant, reliable, and timely information to reduce the risks of information asymmetry. This study employs a descriptive qualitative method with inductive data analysis, highlighting the importance of implementing reporting standards such as IFRS and PSAK, as well as the role of regulatory bodies like OJK in ensuring corporate compliance. The findings reveal that robust regulations enhance investor confidence, create an inclusive investment environment, and promote capital market stability. Despite challenges in regulatory implementation, the harmonization of international standards and stricter supervision can strengthen investor protection. This study recommends the development of adaptive regulations and stringent law enforcement to ensure fairness in capital markets.